The Specificity of Airport Magazines as Custom Publishing Press Roles, Functions and Research Tools - Gawroński, Sławomir; Piątkiewicz, Paweł (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian] The article refers to a relatively new, yet dynamically developing phenomenon, which is airport magazines. In the age of the decline of traditional printed press, any projects involving publishing free printed magazines might seem bound to fail. However, many airports are successfully publishing and developing their own magazines. Most typically they resemble information and entertainment press, but they also evidently have a promotional role. Therefore, they should be considered as marketing communication instruments. This ambiguity makes one reflect on what those magazines really are – a press publishing phenomenon or an indirect marketing influence tool? This article aims to answer the above research question. The applied methodology consists not only of literature review and desk research, but also market analysis and one of the basic press research tools – content analysis. The authors discuss the following factors: conditions of development of airport press, including the Polish market; characteristics of airport magazines which allow them to be classified as custom publishing; functions of airport press and its role within social communication.